Textile fibres from the Caleta Vitor Archaeological Complex, northern Chile - Martens, Tracy (Archaeological Textiles Review, 2021)
This article examines fibre procurement, fibre technologies and type preferences at northern Chile’s Caleta Vitor archaeological complex – a coastal site with archaeological deposits representing more than 10,000 years of occupation. Data obtained from textile analysis, stable isotopes, and historical documents provided evidence of a marine subsistence economy heavily reliant on composite fibre implements, highlighting the early predominance of plant fibres, along with camelid fibres and the introduction of Gossypium barbadense (cotton) in the Formative Period. The study also provides evidence of a previously unknown local camelid fibre source, challenging the long-held hypothesis that camelid fibre at low altitude sites is a proxy for trade with high altitude populations.